Effect of nitric oxide synthase inhibitor and electro-acupuncture in experimentally induced acute spinal cord injury in rabbits - GOPINATHAN, A; PAWDE, A M; SINGH, K; ., AMARPAL; AITHAL, H P; KINJAVDEKAR, P; SHARMA, A K (The Indian Journal of Animal Sciences, 2011)
A model of acute spinal cord trauma was created by inflicting injury at the level of L1-L2 inter-vertebral space in 24 New Zealand White rabbits of either sex; steroid methyl prednisolone sodium succinate, nitric oxide synthase inhibitor L-NAME, electroacupuncture and a combination of L-NAME and electro-acupuncture were administered after injury and were evaluated for changes in clinical and hematological parameters along with changes in plasma triglycerides, insulin, glucose, cortisol, blood electrolytes, motor recovery, and histopathology of spinal cord. L-NAME alone or when combined with electro-acupuncture was better to block pathological changes in spinal cord compared to other groups, whereas, motor recovery was highest in electro-acupuncture treated rabbits. There were no significant changes in the mediators of stress or blood electrolytes. Â